Septal-to-basal ventricular peak activation time determined by vectorcardiography as a potential new pre-screening parameter for preclinical dilated cardiomyopathy in Doberman Pinschers - Gheeraert, Margot; Wess, Gerhard; Mampaey, Gitte; Eberhard, Jenny; Gheeraert, Peter; De Pooter, Jan; Duchateau, Luc; Smets, Pascale (Frontiers in Veterinary Science, 2025)
BackgroundEarly diagnosis of preclinical dilated cardiomyopathy (DCM) remains challenging in primary veterinary medicine due to the need for echocardiography and 24-h Holter electrocardiogram (ECG) recording. A readily available pre-screening tool to identify dogs at high risk could optimize current screening practice. Electrocardiographic methods have not been investigated for this purpose. Vectorcardiographic septal-to-basal ventricular peak activation time (SB-VPAT) was investigated in a preliminary pilot study. We hypothesize that SB-VPAT is a sensitive parameter for detection of systolic dysfunction due to preclinical DCM stage B2 and correlates with left ventricular size and function in Doberman Pinschers.AnimalsOne hundred and twenty-two Doberman Pinschers (98 control and 24 with systolic dysfunction due to preclinical DCM).MethodsProspective cross-sectional study. All dogs underwent echocardiography, three-minute six or 12-lead ECG and RELF ECG. Based on echocardiographic evaluation, dogs were classified into a control group (including apparently healthy dogs and dogs with ventricular arrhythmia’s only) or a group with systolic dysfunction associated with preclinical DCM stage B2. ROC curves of SB-VPAT and its correlation with left ventricular size and function were analyzed.ResultsSB-VPAT ≥33.5 ms had a sensitivity of 94.4% and specificity of 83.6% for the detection of systolic dysfunction due to preclinical DCM stage B2 (AUC 0.954, SD 0.022). Furthermore, SB-VPAT was strongly correlated with the left ventricular systolic diameter, systolic volume index and moderately inversely correlated with EF.Conclusions and clinical importanceIn conclusion, SB-VPAT is a sensitive parameter to detect systolic dysfunction associated with preclinical DCM stage B2. Further investigation of its diagnostic potential compared to or in combination with other tools in a primary care veterinary setting is warranted.